Humanitarian and Beyond States Diplomacy: Society as an Emerging Global Actor - Afifi, Abdullah A; Al-Hadrami, Syarif; Eliza, Mona (Perwakilan: Journal of Good Governance, Diplomacy, Customary Institutionalization and Social Networks, 2025)
The evolution of global interaction in the 21st century reveals a widening gap between the complexity of contemporary crises and the capacity of traditional political diplomacy to address them. Geopolitical rivalries, institutional stagnation, and resource-extractive economic models have created a climate of diplomatic fatigue, where state-centered responses often fall short of delivering timely or humane solutions. Within this vacuum, civil society has emerged as a dynamic and influential actor capable of reshaping global engagement. Humanitarian organizations, volunteer networks, faith-based groups, and transnational advocacy coalitions now mobilize across borders to address urgent human needs, challenge injustices, and promote shared ethical norms. This paper conceptualizes “humanitarian and beyond-states diplomacy” as an alternative paradigm in which diplomatic influence is exercised not only through formal institutions but through societal initiative, moral persuasion, and collective action. It examines how civil society has moved from the periphery to the center of global affairs by negotiating humanitarian access, advocating for vulnerable populations, and generating new norms of solidarity and responsibility. Rather than operating within the limits of state sovereignty or economic interest, these actors draw legitimacy from empathy, global citizenship, and the moral urgency of human protection. The study argues that humanitarian diplomacy from below offers a transformative approach to international cooperation, one capable of renewing compassion, rebuilding trust, and addressing crises that have outpaced traditional diplomatic mechanisms. By analyzing this shift, the paper underscores the rising significance of society as an emerging global actor and highlights the potential of humanitarian engagement to redefine the future of diplomacy.